Carotid Ultrasonography Can Identify Stroke Patients Ineligible for Intravenous Thrombolysis Therapy due to Acute Aortic Dissection. Issue 4 (16th December 2014) - Hama, Yuka; Koga, Masatoshi; Tokunaga, Keisuke; Takizawa, Hotake; Miyashita, Kotaro; Iba, Yutaka; Toyoda, Kazunori
ABSTRACT Acute aortic dissection is the most common acute aortic condition requiring urgent surgical therapy. Due to lack of typical symptoms, it is sometimes difficult to identify acute aortic dissection causing ischemic stroke. We report a case of a patient with acute ischemic stroke who was deemed ineligible for intravenous recombinant tissue plasminogen activator treatment based on a finding of acute aortic dissection detected by carotid ultrasonography. After urgent aortic replacement surgery, the patient recovered with no neurological deficit. This case underscores the crucial role of carotid ultrasonography for the investigation of possible underlying acute aortic dissection when considering the use of intravenous recombinant tissue plasminogen activator therapy for hyperacute stroke.